2012
DOI: 10.1177/1045389x12461696
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of vibration reduction using shape memory alloys

Abstract: Smart materials have a growing technological importance due to their unique thermomechanical characteristics. Shape memory alloys belong to this class of materials being easy to manufacture, relatively lightweight, and able to produce high forces or displacements with low power consumption. These aspects could be exploited in different applications including vibration control. Nevertheless, literature presents only a few references concerning the experimental analysis of shape memory alloy dynamical systems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Savi et al [18] discussed the general aspects of adaptive behavior of ATVA. Aguiar et al [24] confirmed these conclusions from an experimental point of view.…”
Section: Numerical Simulationssupporting
confidence: 78%
“…Savi et al [18] discussed the general aspects of adaptive behavior of ATVA. Aguiar et al [24] confirmed these conclusions from an experimental point of view.…”
Section: Numerical Simulationssupporting
confidence: 78%
“…The former means returning back to the predetermined shapes upon heating. The latter is related to the large amount of inelastic deformation which can be recovering after unloading (Aguiar and Savi, 2013). Composites are being increasingly used in aerospace, marine and civil due to the advantages they offer.…”
Section: Introductionmentioning
confidence: 99%
“…This phase change can be manipulated by controlling the temperature of the SMA [52][53][54][55][56], such as through an electrical current [57]. Many researchers have taken advantage of this unique property to develop adaptive TMDs in active and semi-active control schemes to enhance the damping capabilities of the TMDs [58][59][60][61]. However, SMAs have been never used in a PTMD before.…”
Section: Introductionmentioning
confidence: 99%